Energy Geopolitics in the Transition Era: Indonesia's Strategy in Creating Energy Security Amidst Global Crisis - Azzahra, Adelia (Politeknik Siber Cerdika Internasional, 2025)
Global dependence on fossil energy faces serious challenges in the era of energy transition, marked by geopolitical crises such as the Russia-Ukraine conflict, oil price volatility and global decarbonization pressures. Indonesia, as a developing country with fossil energy reserves and ambitious targets for the transition to renewable energy, is in a strategic but complex position. Energy security is now a national issue as well as part of international geopolitical strategy. This research aims to analyze Indonesia's strategy in creating energy security amid global dynamics, as well as evaluate the geopolitical implications of the national energy transition policy. This research uses a qualitative approach with a policy study method and analysis of official documents such as Presidential Regulation No. 112 of 2022, the National Energy General Plan (RUEN), as well as IEA and IRENA reports. A geopolitical analysis framework approach was also used to assess Indonesia's position in the global energy supply chain. The results show that Indonesia is developing a dual-track strategy: strengthening domestic energy infrastructure based on renewable energy and expanding energy diplomacy with strategic partners such as China, Japan and the Gulf countries. However, major challenges still exist in the form of investment imbalances, coal dependence, and local political resistance to energy transition projects. Therefore, Indonesia's energy security strategy in the transition era requires synergy between national policies and global geopolitics in an adaptive and collaborative manner.